Tracking historical changes in trustworthiness using machine learning analyses of facial cues in paintings - Lou Safra (Nature Portfolio, 2020)
Quantifying how social trust evolved throughout history can help us understand the long-run dynamics of our societies. Here, the authors show an increase in displays of trustworthiness, using a face processing algorithm on early to modern European portraits.